Correction: Facile synthesis of stable, water soluble, dendron-coated gold nanoparticles. Issue 30 (21st July 2017) - Enciso, Alan E.; Doni, Giovanni; Nifosì, Riccardo; Palazzesi, Ferruccio; Gonzalez, Roberto; Ellsworth, Ashley A.; Coffer, Jeffery L.; Walker, Amy V.; Pavan, Giovanni M.; Mohamed, Ahmed A.; Simanek, Eric E.
Abstract : Correction for 'Facile synthesis of stable, water soluble, dendron-coated gold nanoparticles' by Alan E. Enciso, et al., Nanoscale, 2017, 9, 3128–3132.